La percepción de una marca en inglés y su efecto en la decisión de compra: supermercado Tottus en el CC Jockey Plaza - Nature’s Heart - Honderman Ubillus, Samantha (2023)
In the present research work, the relationship between the perception of clients in front of Nestlé's Nature's Heart brand, which has a name in English, and how this name in another language influences the client's purchase decision will be reviewed. . The study will focus on the category with the highest sales, vegetable drinks, and on buyers from 20 to 30 years of age from NSE A, B and C who attend Tottus at the Jockey Plaza Shopping Center. The extent to which product differentiation conditions the positioning of plant-based beverages in the consumer's mind will be explored. Likewise, it will be discovered if the perception of superior quality of the products comes from the English name of the brand. Finally, it will be defined if the perceived value is the most important benefit that guides the consumer's purchase decision.